PERLINDUNGAN HUKUM TERHADAP KONSUMEN SEBAGAI PENGGUNA JASA PENERBANGAN : Studi Putusan Mahkamah Agung Nomor : 975 K/Pdt/2019 - Muhamad Bilal Saputra (2021)
Protection provided by law is an action or effort to protect the public from arbitrary acts. The problem in this study is regarding the judge's considerations in the PN Decision Number 169/Pdt.G/2017/PN/Tng and the PT's Decision Number 9/Pdt/2018/PT. Btn. which was canceled by the decision of the Supreme Court Number: 975 K/Pdt/2019. Another problem is regarding the suitability of the Supreme Court's Decision Number: 975 K/Pdt/2019 with the Consumer Protection Act and the Aviation Law. The research method used is normative research with a case approach and a statutory approach. Normative research is carried out by examining legal materials in the form of laws and regulations which are the basic material to be studied using qualitative analysis. The results of this study indicate that there are differences in the judgment of judges at the District Court, High Court, and Supreme Court regarding acts of default and acts against the law. Then the Supreme Court's decision has also been in accordance with Law Number 1 of 2009 concerning Aviation and Law Number 8 of 1999 concerning Consumer Protection.